Peran Kepemimpinan Visioner terhadap Keterlibatan Kaum Muda dalam Gereja Katolik - Maretio, Yehezkiel Divo (Institutum Ioannis Mariae Vianney Surabayanum, 2025)
The involvement of young people in the life of the Catholic Church faces serious challenges amid the VUCA era (volatility, uncertainty, complexity, ambiguity). The low participation of Millennials and Generation Z raises concerns about the continuity of the Church’s mission. This study investigates the role of visionary leadership in encouraging youth involvement in the Catholic Church. The purpose of this research is to analyze the influence and relevance of visionary leadership in addressing the dynamics of youth engagement and to formulate leadership strategies aligned with their characteristics. The findings show that visionary leadership—emphasizing clear communication, adaptability to change, and the ability to provide direction and meaning in action—is highly effective in engaging young people. Visionary leaders serve as direction-setters, change agents, spokespersons, and coaches who integrate Church values with the pragmatic and digital native nature of today’s youth. In conclusion, visionary leadership is not only relevant but a strategic necessity to strengthen the active participation of younger generations in the Church. As such, the Church can remain contextual and vibrant in facing contemporary challenges.